Mitochondrial DNA Analysis from Exome Sequencing Data Improves Diagnostic Yield in Neurological Diseases. Issue 6 (1st April 2021) - Poole, Olivia V.; Pizzamiglio, Chiara; Murphy, David; Falabella, Micol; Macken, William L.; Bugiardini, Enrico; Woodward, Cathy E.; Labrum, Robyn; Efthymiou, Stephanie; Salpietro, Vincenzo; Chelban, Viorica; Kaiyrzhanov, Rauan; et al.
Abstract : A rapidly expanding catalog of neurogenetic disorders has encouraged a diagnostic shift towards early clinical whole exome sequencing (WES). Adult primary mitochondrial diseases (PMDs) frequently exhibit neurological manifestations that overlap with other nervous system disorders. However, mitochondrial DNA (mtDNA) is not routinely analyzed in standard clinical WES bioinformatic pipelines. We reanalyzed 11, 424 exomes, enriched with neurological diseases, for pathogenic mtDNA variants. Twenty‐four different mtDNA mutations were detected in 64 exomes, 11 of which were considered disease causing based on the associated clinical phenotypes. These findings highlight the diagnostic uplifts gained by analyzing mtDNA from WES data in neurological diseases. ANN NEUROL 2021;89:1240–1247